(untitled) (Damascus University Journal of agriculture sciences, 2026)
An experiment was conducted in the agricultural scientific research center in Petima, Damascus Countryside Governorate, during the 2022-2023 planting season, to study the effect of four irrigation trials (I0: rain fed agriculture, I1: two flag, I2: three flag,I3: complete irrigation) according to five fertilizer trials (F1: Recommended mineral fertilizer; F2: half the fertilizer recommended dose+ spray algae 1extracts1.5kg .ha-1 + spray humic acid 2k.ha-1,F3: half the fertilizer recommendation+ spray humic acid 2 kg .ha-1,F4: half the fertilizer recommendation+ spray algae fertilizer 1.5kg .ha-1,F5:spray algae fertilizer1.5kg .ha-1 and humic acid1.5kg .ha-1) in some growth and productivity traits for Quinoa Q26 model. The experiment was designed according to a randomized complete block design (RCBD) in the order of the split blocks, with 3 replications. The results showed significant differences between the studied treatments and their interactions. Where complete irrigation (I3) excelled in developmental traits and achieved the least number of days needed until maturity (157.00days), plant length(106.60cm), seed yield (5246kg.ha-1)and number of panicles in plant(16 panicle. plant-1) the number of seeds per plant(15643.4seed.plant-1), supplement irrigation, (I2) excelled in developmental traits and achieved the thousand seeds(2.86gr),bio-yield(13960kg .ha-1), while fertilization treatment (F2) excelled in all productive traits and achieved the highest plant length(106.60cm), average number of panicles in plant (15.50 panicle.Plant-1),the number of seeds per plant(17096.25seed. plant-1) and the weight of a thousand seeds(3.01gr).the seed yield(6502kg.ha-1), and bio-yield(18000kg.ha-1).While for the interaction of the studied treatments, cultivation by complete irrigation (I3)with the application of fertilization treatment(F2)gave the highest average plant length (109cm),number of panicles in plant(16panicle.plant-1), number of seeds per plant(26134seed. plant-1), and the seed yield (9511kg .ha-1).